Gravity reference at the Argentinean–German Geodetic Observatory (AGGO) by co-location of superconducting and absolute gravity measurements - Antokoletz, Ezequiel D.; Wziontek, Hartmut; Tocho, Claudia N.; Falk, Reinhard (Journal of geodesy, 2020)
The Argentinean–German Geodetic Observatory (AGGO) is a fundamental geodetic observatory located close to the city of La Plata, Argentina. Two high-precision gravity meters are installed at AGGO: the superconducting gravimeter SG038, which is in operation since December 2015, and the absolute gravimeter FG5-227, which has provided absolute gravity measurements since January 2018. By co-location of gravity observations from both meters between January 2018 and March 2019, calibration factor and instrumental drift of the SG038 were determined. The calibration factor of the SG038 was estimated by different strategies: from tidal models, dedicated absolute gravity measurements over several days and a joint approach (including the determination of the instrumental drift) using all available absolute gravity data. The final calibration factor differs from the determination at the previous station, the transportable integrated geodetic observatory, in Concepcion, Chile, by only 0.7‰, which does not imply a significant change. From the combined approach also the mean absolute level of the SG was determined, allowing to predict absolute gravity values from the SG at any time based on a repeatability of 12 nm / s 2 for the FG5-227 at AGGO. Such a continuous gravity reference function provides the basis for a comparison site for absolute gravimeters in the frame of the international gravity reference frame for South America and the Caribbean. However, it requires the assessment of the total error budget of the FG5-227, including the link to the international comparisons, which will be subject of future efforts.